Distribution of P2O5 between Phosphorus‐Enrichment Phase and Matrix Phase in Phosphorus‐Containing Slag. Issue 9 (25th February 2013) - Zhou, Han‐Mei; Bao, Yan‐Ping; Lin, Lu
Abstract: In order to make better recovery utilization of the phosphorus in the steel slag, and as P2 O5 mainly exists in phosphorus‐enrichment phase and matrix phase of steel slag, it is a must to study the distribution of P2 O5 between those two phases in the phosphorus‐containing slag and its related influencing factors. Heat experiments were conducted in this research, and the final slag was analyzed with the method of scanning electron microscope (SEM) + energy disperse spectroscopy (EDS). Then L p, r p, and C p in both phosphorus‐enrichment phase and matrix phase were calculated, respectively. From this study, is has been found that CaO% in matrix phase, the basicity of slag and mass fraction of P2 O5 in both phosphorus‐enrichment phase and matrix phase influence the distribution ratio of P2 O5 in the slag. Adding CaF2 also has effect on P2 O5 partition while adding MgO and MnO has no obvious effect. Besides, for the low content of T.Fe in matrix phase, there is no linear relationship between L p orγ _P_2 O_5 and T.Fe in matrix phase. Abstract : To make better recovery utilization of the phosphorus in the phosphorus‐containing slag, the influencing factors on distribution of P2 O5 between the phosphorus‐enrichment phase and the matrix phase in the slag are analyzed in this study. It has been found out that %(CaO) in the matrix phase, adding P2 O5 or CaF2 and increasing the basicity of slag, are the main influencing factors.